Purification, characterization, and cDNA cloning of an NADPH-cytochrome P450 reductase from mung bean. - Shet, M S (1993)
We report here the isolation and deduced amino acid sequence of the flavoprotein, NADPH-cytochrome P450 (cytochrome c) reductase (EC 1.6.2.4), associated with the microsomal fraction of etiolated mung bean seedlings (Vigna radiata var. Berken). An 1150-fold purification of the plant reductase was achieved, and SDS/PAGE showed a predominant protein band with an apparent molecular mass of approximately 82 kDa. The purified plant NADPH-P450 reductase gave a positive reaction as a glycoprotein, exhibited a typical flavoprotein visible absorbance spectrum, and contained almost equimolar quantities of FAD and FMN per mole of enzyme. Specific antibodies revealed the presence of unique epitopes distinguishing the plant and mammalian flavoproteins as demonstrated by Western blot analyses and inhibition studies. Peptide fragments from the purified plant NADPH-P450 reductase were sequenced, and degenerate primers were used in PCR amplification reactions. Overlapping cDNA clones were sequenced, and the deduced amino acid sequence of the mung bean NADPH-P450 reductase was compared with equivalent enzymes from mammalian species. Although common flavin and NADPH-binding sites are recognizable, there is only approximately 38% amino acid sequence identity. Surprisingly, the purified mung bean NADPH-P450 reductase can substitute for purified rat NADPH-P450 reductase in the reconstitution of the mammalian P450-catalyzed 17 alpha-hydroxylation of pregnenolone or progesterone.